Risk factors for acute myocardial infarction in Central India: A case-control study - Sanjay P Zodpey; Sunanda N Shrikhande; Himanshu N Negandhi; Suresh N Ughade; Prashant P Joshi (Wolters Kluwer Medknow Publications, 2015)
Background: Atherosclerosis is a multi-factorial disease involving the interplay of genetic and environmental factors. Studies highlighting the public health importance of risk factors like chronic infections causing acute myocardial infarction (AMI) in the Indian context are scarce. This study was undertaken to study the association of socio-demographic and life-style factors with acute myocardial infarction in central India. Materials and Methods: The cases and controls were group-matched for age, gender, and socio-economic status. A blinded research associate administered the study questionnaire. We performed an unconditional multiple logistic regression analysis. Results: The case-control study included 265 cases of AMI and 265 controls. The results of final model of logistic regression analysis for risk factors of AMI included 11 risk factors at α = 0.05. They were waist hip ratio, body mass index, stress at home in last 1 year, hypertension, family history of CHD, past history of gingival sepsis, tobacco smoking, raised total serum cholesterol, Chlamydia pneumoniae, Helicobacter pylori and raised C-reactive protein. Conclusion: The findings confirm the role of conventional risk factors for cardiac disease and highlight need for research into the association between chronic infections with AMI.